Dampak Desain Interior dan Ambience Warung Kopi terhadap Keputusan Generasi Z - Arifin , Sultonul; Agustina, Rohmatin; Djazuli, Raden Achmad (Jurnal Ekonomi Pertanian dan Agribisnis, 2025)
This research aims to analyze the influence of coffee shop interior design and ambience on the purchasing decisions of Generation Z consumers at Central Caffe Gresik. Using a survey method with 100 respondents, this study explores how elements of interior design and ambience affect visit frequency, visit duration, purchase amount, and intention to return and recommend. The results indicate that both interior design and ambience have a significant influence on purchasing decisions, with ambience having a slightly stronger impact. These findings provide valuable insights for coffee shop businesses in designing strategies to attract and retain Generation Z customers.